TAHU SUMEDANG: Digital Public Service Implementation (A Studi at Regional Government of Sumedang Regency) - Sulastri, Lalas (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
Digital transformation in public service delivery has become a key strategy in promoting government efficiency, effectiveness, and transparency. This study aims to analyze the effectiveness of implementing the TAHU SUMEDANG digital public service portal in the Sumedang Regency and identify the challenges encountered in its application. The research adopts a qualitative approach using a case study method, involving in-depth interviews with 10 key informants, participatory observations, and document analysis of regional public service policies and reports from 2023. The findings reveal that the TAHU SUMEDANG portal has increased service speed by up to 40% compared to the pre-digitalization period and expanded public access to administrative services, with a 65% increase in active users over the past year. Furthermore, service transparency has improved through an online service tracking system accessed by more than 12,000 users. These findings align with previous studies by Nugroho (2021) and Pratama and Wahyudi (2022), demonstrating that adopting digital technologies in local public services can accelerate bureaucratic responsiveness and enhance citizen satisfaction. However, the implementation still faces significant challenges, including limited digital infrastructure in 23% of peripheral villages, low digital literacy, especially among older people, and resistance from 30% of government staff who are not yet accustomed to the digital system. Compared to similar programs such as "SIPANDA" in Banyuwangi Regency and "Jakarta Smart City," Sumedang still has room for improvement regarding data integration and service simplification. In conclusion, digitalization through the TAHU SUMEDANG portal has positively impacted the quality of public services, yet it requires further strengthening in infrastructure, digital literacy, and staff capacity. The results of this study are expected to serve as strategic input for local governments in formulating inclusive, adaptive, and sustainable digital public service policies.